Pengaruh Pemilihan Umum Tahun 2019 terhadap Abnormal Return dan Trading Volume Activity di Bursa Efek Indonesia (Studi Perusahaan yang Tercatat dalam Jakarta Islamic Index 70) - Amalia, Luthfina Zahrotul; Santosa, Purbayu Budi (Diponegoro Journal of Islamic Economics and Business, 2022)
The political events can affect the condition of a capital market because it is related to the national economic stability. One of the events that affects the capital market is the general election. The 2019 general election was the first time that presidential and legislative elections were held at the same time in Indonesia. However, the high public enthusiasm, which reached 81%, was not followed by the increase of IDX Composite (IHSG) throughout April 2019. The IDX Composite fluctuated and tended to decline. This research is an event study that aims to analyze the differences in abnormal return and trading volume activity of stock market between the period before and after the general election held on April 17, 2019.This study uses quantitative methods by using secondary data, published on the Indonesia Stock Exchange website. The population of the data used is the 70 companies listed on Jakarta Islamic Index 70 (JII70), then the sample was taken using the purposive sampling as many as 58 of 70 companies. The event period is 20 days length, 10 days before the election, and 10 days after the election. The analysis uses non-parametcric different’s test Wilcoxon Signed Rank Test. The result showed that there were no significant differences in abnormal return, but there were significant differences in trading volume activity between before and after the general election April 17, 2019.